Blood Donation Management System Using Progressive Web Application - Muhammad Firdaus, Zakaria (Universiti Malaysia Sarawak (UNIMAS), 2020)
Blood Donation Management System is a system that help the staff in handling anything related to blood donation. It also acts a database as it stored all the data of the blood donor online. This will avoid from the lost of blood donor data and help the staff in retrieving a specific data of blood donor out of all blood donor record. Currently, the staff needs to go through a lot of record in order to find the record that they are looking for. This system helps to ease the process of searching for the required record. The system also helps the blood donor in organizing their schedule to join a blood donation event as they will be a blood donation event section. The medic the upcoming event on the event section and can be reviewed by the blood donor. This system will be built as a progressive web application where it will be compatible to be used using mobile phones, table, personal computer, and laptop. As long as the device have access to a browser, the device a good to go to use this system. The methodology being used in developing this system is borrowed by the concept in the scrum methodology.